A particulate graphite recarburizer and methods of making and using the same
Patent Information
- Application Number
- CN202611049682.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]本发明针对现有技术的不足,通过液相共分散使碳化硅微粒定位于每个石墨颗粒表面,形成界面亲密化复合结构,解决了干法机械混合中碳化硅仅随机覆盖少数石墨表面、利用效率低的问题,同时提高了碳收得率
(1)采用经浮选的鳞片石墨为碳源,不经化学提纯,原料的固定碳含量不小于90%即可使用,生产成本降低,环境友好。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of iron and steel metallurgy technology, specifically relating to a granular graphite recarburizing agent for steelmaking, its preparation method, and its application method. Background Technology
[0002] In the converter steelmaking process, recarburizers are used to replenish the carbon content of molten steel to adjust the carbon index of the finished steel. Silicon carbide is a commonly used auxiliary component in recarburizers. In molten steel, it is firstly wetted and dissolved by liquid iron to form Fe-Si-C melt, promoting the wetting of the graphite surface by the molten steel; secondly, it forms local deoxidation micro-regions around the graphite, reducing the oxidation and burning loss of graphite carbon.
[0003] Existing recarburizing agents involve dry mechanical mixing of graphite and silicon carbide powder followed by granulation. In this process, both powders maintain independent particle morphology, with silicon carbide microparticles randomly distributed among the graphite particles. The wetting-promoting and deoxidation-protecting effects of silicon carbide are only effective on the surface of a small number of directly adjacent graphite particles; most graphite surfaces remain intrinsically non-wetting in the molten steel, resulting in low silicon carbide utilization.
[0004] To address the aforementioned issues, one improvement approach involves chemically purifying the graphite raw material. By increasing the fixed carbon content and crystal integrity of the graphite, the formation of an interfacial gas film during contact with molten steel is reduced, thereby improving wetting. However, this approach is complex, involving strong oxidizing acids and highly toxic hydrofluoric acid, requiring equipment with high corrosion resistance and incurring significant waste acid treatment costs. Another approach involves adding large amounts of metal powder (such as high-carbon ferromanganese or high-carbon ferrochrome) to the carburizing agent. The high density of the metal slows down particle flotation and prolongs carbon dissolution time. However, this approach introduces hetero-alloying elements such as manganese and chromium into the molten steel, interfering with the control of steel composition and is only suitable for specific steel grades.
[0005] Therefore, how to enable silicon carbide microparticles to actively position themselves on the surface of each graphite particle under the condition of using ordinary commercial graphite, so as to cover all graphite particles with wetting promotion and deoxidation protection, without introducing heterogeneous alloying elements, is a problem that has not yet been solved by existing technology. Summary of the Invention
[0006] This invention addresses the shortcomings of existing technologies by using liquid-phase co-dispersion to position silicon carbide microparticles on the surface of each graphite particle, forming a closely integrated composite structure at the interface. This solves the problem of low utilization efficiency caused by silicon carbide only randomly covering a few graphite surfaces in dry mechanical mixing, while also improving carbon yield.
[0007] This invention provides a granular graphite recarburizer, prepared from the following dry materials in the following weight proportions: 80-85 parts of natural flake graphite and 12-20 parts of silicon carbide micro powder; the fixed carbon content of the natural flake graphite is not less than 90%, and the particle size D50 is 0.15-0.50 mm; the purity of the silicon carbide micro powder is not less than 80%, and the particle size D50 is not greater than 0.01 mm; the recarburizer further includes polyvinyl alcohol and polyvinylpyrrolidone, the amount of polyvinyl alcohol added is 2%-5% of the total weight of the above dry materials on a solid basis, and the amount of polyvinylpyrrolidone added is 0.1%-0.5% of the weight of natural flake graphite; the particle size of the recarburizer is 8-18 mm.
[0008] Preferably, the degree of alcoholysis of the polyvinyl alcohol is 85% to 95%, and the degree of polymerization is 500 to 2000.
[0009] Preferably, the degree of graphitization of the natural flake graphite is not less than 90%. This invention also provides a method for preparing granular graphite recarburizer, comprising the following steps: (1) Natural flake graphite, water, and polyvinylpyrrolidone are added to a stirred ball mill and wet-milled until the particle size D50 of the natural flake graphite is 0.15-0.50 mm to obtain graphite ink slurry; the amount of polyvinylpyrrolidone added is 0.1%-0.5% of the weight of the natural flake graphite; (2) Add silicon carbide micro powder to the graphite slurry obtained in step (1), and stir in a high-speed disperser at 1000-3000 rpm for 15-45 minutes to obtain a graphite-silicon carbide co-dispersed slurry; the particle size D50 of the silicon carbide micro powder is not greater than 0.01 mm and the purity is not less than 80%; (3) The co-dispersed slurry obtained in step (2) is dehydrated by a filter press at a pressure of 0.5 to 2.0 MPa to a moisture content of 20% to 30% to obtain filter cake; (4) According to the dry material weight ratio, the filter cake obtained in step (3) and polyvinyl alcohol powder are put into a kneader and kneaded for 15 to 45 minutes to obtain a mixture; the degree of alcoholysis of the polyvinyl alcohol powder is 85% to 95%, the degree of polymerization is 500 to 2000, and its addition amount is 2% to 5% of the total dry material weight on a solid basis; (5) The mixture obtained in step (4) is fed into an extrusion granulator, extruded through a template with an aperture of 8-18 mm, and granulated to obtain wet granules; (6) Dry the wet particles obtained in step (5) until the moisture content is less than 1% to obtain the granular graphite recarburizer.
[0010] Preferably, the drying in step (6) is carried out in a multi-stage manner: first, the particles are dried at 60-90°C until the moisture content is no more than 5%, and then dried at 110-120°C until the moisture content is less than 1%.
[0011] This invention also provides a method for using granular graphite recarburizer, comprising the following steps: In the initial stage of converter tapping, when the tapping volume reaches 0% to 30% of the total tapping volume, 20% to 40% of the total recarburizing agent weight is added to the ladle; the remaining 60% to 80% is added to the ladle with the steel flow via a feeder during the converter tapping process; the total amount of recarburizing agent added is 3 to 7 kg / t steel.
[0012] Preferred and applicable tapping conditions are: carbon content in molten steel of 0.05% to 0.15%, total oxygen content in steel of 70 ppm to 150 ppm, and tapping temperature of 1610℃ to 1670℃.
[0013] The beneficial effects of this invention are: (1) Using flotation-processed flake graphite as the carbon source, without chemical purification, the raw material can be used with a fixed carbon content of not less than 90%, which reduces production costs and is environmentally friendly.
[0014] (2) By using liquid phase co-dispersion and pressure filtration processes, silicon carbide particles are positioned on the surface of graphite particles facing the pores. The wetting promotion and deoxidation protection of silicon carbide changes from randomly covering a few graphite surfaces to covering each graphite particle, and the utilization rate of silicon carbide is greatly improved.
[0015] (3) The formula contains only natural flake graphite, silicon carbide and organic process additives. Polyvinyl alcohol and polyvinylpyrrolidone are completely pyrolyzed at the temperature of molten steel. Carbon dissolves in molten steel and becomes an effective component for increasing carbon content. Hydrogen, nitrogen and oxygen escape in gaseous state. No heterogeneous alloying elements such as silicon, manganese, chromium and molybdenum are introduced into molten steel. It is suitable for increasing carbon content of all steel grades.
[0016] (4) The present invention uses wet grinding and co-dispersion in an aqueous medium, without the volatilization of organic solvents and dust. Detailed Implementation
[0017] The present invention will be further described in detail below with reference to the embodiments, but the scope of protection of the present invention is not limited to the scope of the embodiments.
[0018] In the following examples, the natural flake graphite used was commercially available flake graphite, passed through a 2 mm standard sieve, with a fixed carbon content of 95%, a graphitization degree of 93%, and a moisture content of less than 0.5%; the silicon carbide micro powder had a purity of 99% and a D50 of 8 μm; the polyvinyl alcohol used was commercially available PVA 17-88 type, with a degree of alcoholysis of 88% and a degree of polymerization of 1700; the polyvinylpyrrolidone used was commercially available PVP K30; and the water was industrial deionized water.
[0019] Example 1 1) 850 g of natural flake graphite, 1500 mL of water, and 1.7 g of polyvinylpyrrolidone were added to a stirred ball mill. The grinding media consisted of 10 mm diameter zirconia balls with a filling rate of 60%. The mill was wet-milled at 200 rpm for 40 minutes, and the graphite particle size distribution (D50) was measured to be 0.18 mm, yielding a graphite ink slurry. (2) Add 150 g of silicon carbide micro powder to the graphite ink slurry and stir at 2000 rpm for 30 minutes in a high-speed disperser to obtain graphite-silicon carbide co-dispersed slurry; (3) The co-dispersed slurry is fed into a filter press and dehydrated to a moisture content of 25% under a pressure of 1.0 MPa to obtain filter cake; (4) Add the filter cake and 30 g of polyvinyl alcohol powder into a kneader and knead for 30 minutes to obtain the mixture; (5) The mixture is fed into an extrusion granulator and extruded through a template with a diameter of 15 mm. The pellet length is controlled to be 12-18 mm to obtain wet pellets. (6) Place the wet granules in an oven and dry them at 80°C for 2.5 hours until the moisture content is about 4%, then dry them at 110°C for 1.5 hours until the moisture content is 0.5%, and the finished product is obtained. The particle size of the finished product is 8-18 mm.
[0020] Example 2 (1) 800 g of natural flake graphite, 1600 mL of water and 4.0 g of polyvinylpyrrolidone were added to a stirred ball mill. The grinding media were 10 mm diameter zirconia balls with a filling rate of 60%. The graphite particles were wet-milled at 250 rpm for 25 minutes, and the graphite particle D50 was 0.15 mm, resulting in a graphite ink slurry. (2) Add 200 g of silicon carbide micro powder to the graphite ink slurry and stir at 1500 rpm for 45 minutes in a high-speed disperser to obtain a co-dispersed slurry; (3) The co-dispersed slurry was dewatered to a moisture content of 20% by a filter press at a pressure of 2.0 MPa to obtain filter cake; (4) Add the filter cake and 20 g of polyvinyl alcohol powder to a kneader and knead for 15 minutes to obtain the mixture; (5) The mixture is fed into an extrusion granulator and extruded through a 12 mm aperture template. The pellets are cut into 10-15 mm lengths to obtain wet pellets. (6) Dry the wet granules at 80°C for 1.5 hours until the moisture content is about 3%, and then dry them at 120°C for 40 minutes until the moisture content is 0.3% to obtain the finished product. The particle size of the finished product is 8-15 mm.
[0021] Example 3 (1) 840 g of natural flake graphite, 1600 mL of water and 0.9 g of polyvinylpyrrolidone were added to a stirred ball mill. The grinding media were 10 mm diameter zirconia balls with a filling rate of 60%. The graphite particles were wet-milled at 180 rpm for 45 minutes, and the graphite particle D50 was 0.35 mm, resulting in a graphite ink slurry. (2) Add 120 g of silicon carbide micro powder to the graphite ink slurry and stir at 3000 rpm for 15 minutes in a high-speed disperser to obtain a co-dispersed slurry; (3) The co-dispersed slurry is dehydrated to a moisture content of 30% by a filter press at a pressure of 0.5 MPa to obtain filter cake; (4) Add the filter cake and 50 g of polyvinyl alcohol powder to a kneader and knead for 45 minutes to obtain the mixture; (5) The mixture is fed into an extrusion granulator and extruded through a template with an aperture of 18 mm. The granules are then cut into pellets with a length of 16-22 mm to obtain wet pellets. (6) Dry the wet granules at 90°C for about 3.5 hours until the moisture content is about 5%, and then dry them at 110°C for about 2 hours until the moisture content is 0.8% to obtain the finished product. The particle size of the finished product is 14-18 mm.
[0022] Example 4 (1) 820 g of natural flake graphite, 1500 mL of water and 2.5 g of polyvinylpyrrolidone were added to a stirred ball mill. The grinding media were 10 mm diameter zirconia balls with a filling rate of 60%. The graphite slurry was obtained by wet milling at 220 rpm for 35 minutes and the graphite particle D50 was 0.50 mm. (2) Add 180 g of silicon carbide micro powder to the graphite ink slurry and stir at 1000 rpm for 40 minutes in a high-speed disperser to obtain a co-dispersed slurry; (3) The co-dispersed slurry was dehydrated to a moisture content of 22% by a filter press at a pressure of 1.5 MPa to obtain filter cake; (4) Add the filter cake and 35 g of polyvinyl alcohol powder to a kneader and knead for 40 minutes to obtain the mixture; (5) The mixture is fed into an extrusion granulator and extruded through a template with an aperture of 18 mm. The pellets are then cut into pellets with a length of 12-18 mm to obtain wet pellets. (6) Dry the wet granules at 80°C for 3.5 hours until the moisture content is about 5%, and then dry them at 110°C for 2 hours until the moisture content is 0.6% to obtain the finished product. The particle size of the finished product is 10-18 mm.
[0023] Comparative Example 1 The same raw materials and proportions as in Example 1 were used: 850g of natural flake graphite, 150g of silicon carbide micro powder, and 30g of polyvinyl alcohol powder. However, the preparation method was changed to dry mechanical mixing. The specific steps were as follows: the graphite powder, silicon carbide powder, and polyvinyl alcohol powder were dry-mixed in a V-type mixer for 30 minutes, water was added and granulated in a disc granulator, and then dried at 110°C until the moisture content was less than 1%.
[0024] The carbon raisers prepared in Examples 1-4 and Comparative Example 1 were subjected to carbon raising tests in a 100-ton converter at a steel plant. The tapping conditions for each test heat are shown in Table 1.
[0025] Table 1. Steel tapping conditions for each embodiment and comparative example heat. The total amount of carbon raiser added was 5 kg / t of steel. At the initial tapping stage, when approximately 20% of the steel had been tapped, 30% of the total carbon raiser was added, with the remaining 70% added via the feeder along with the steel stream. After carbon raising was completed, the final carbon content was measured, and the carbon yield and carbon raiser fluctuation range were calculated. Each example and comparative example underwent a five-heat repeat test, and the average carbon yield and fluctuation range were taken. The results are shown in Table 2.
[0026] Table 2. Carbon enhancement effect of each embodiment and comparative example In the above embodiments and comparative examples, the local anchor point spacing is a calculated value, and the carbon yield and fluctuation range are experimentally measured values. The methods for obtaining each data are as follows.
[0027] The local anchor point spacing refers to the average center-to-center distance between silicon carbide particles within the surface area where graphite particles can contact silicon carbide particles, and is calculated using the following formula.
[0028] Graphite single-particle surface area S (mm²): S = 4π × (D / 2)²; Where D is the median particle size (cm) of the graphite particles, which is determined by a laser particle size analyzer according to the standard GB / T19077-2016 "Particle size distribution by laser diffraction".
[0029] Mass of a single graphite particle, m (g): m = (4 / 3)π × (D / 2)³ × ρa; Where ρa is the density of graphite crystals, taken as 2.2 g / cm³.
[0030] The number of silicon carbide particles N corresponding to a single graphite particle: N = m × (R / n).
[0031] Where R is the weight ratio of silicon carbide to graphite (determined by the formulation). n is the mass (g) of a single silicon carbide particle, calculated using the following formula: n = (4 / 3)π × (d / 2)³ × ρb; Where d is the median particle size (cm) of silicon carbide microparticles, determined by a laser particle size analyzer (GB / T 19077-2016); ρb is the density of silicon carbide, taken as 3.2 g / cm³.
[0032] The surface area A (cm²) of graphite particles that silicon carbide microparticles can contact: A = S × f Where f is the surface area of graphite particles that silicon carbide microparticles can contact, which is determined by the packing structure of graphite particles after pressure filtration, and is taken as an empirical value of 0.25 to 0.40.
[0033] Local average spacing λ (μm) between silicon carbide particles: λ = 10000 × (A / N)^0.5 The calculation results are expressed in "μm", rounded to one decimal place, and prefixed with "~" to indicate that the value is a calculated estimate.
[0034] Taking Example 1 as an example: D = 0.018 cm, S = 1.02 × 10 -3 cm², m = 6.71 × 10 -6 g; R=150 / 850=0.176; d=8 μm=0.0008 cm, n=8.58×10 -10 g, N≈1377; f is taken as 0.30, A=3.06×10 -4 cm², λ≈4.7 μm.
[0035] Carbon recovery rate refers to the ratio of the actual amount of carbon absorbed by the molten steel after the addition of the carburizing agent to the total amount of carbon brought into the molten steel by the carburizing agent, expressed as a percentage, and calculated using the following formula: η = (C2 - C1) × W / (M × C0) × 100% The meanings of the symbols in the formula and how to obtain them are as follows: C1 and C2 were both determined using an infrared carbon-sulfur analyzer, following the standard GB / T 20123-2006 "Determination of Total Carbon and Sulfur Content in Iron and Steel - Infrared Absorption Method After Combustion in a High-Frequency Induction Furnace".
[0036] The method for determining C0 is as follows: Take a sample of the finished carbon refining agent. The fixed carbon content of graphite is determined according to GB / T 3521-2008 "Methods for Chemical Analysis of Graphite". The total carbon content of silicon carbide is determined according to GB / T 16555-2008 "Methods for Chemical Analysis of Carbon-containing and Silicon Carbide Refractory Materials". The carbon content of polyvinyl alcohol and polyvinylpyrrolidone is calculated according to the mass fraction of carbon element in their molecular formula. The carbon content of the above components is weighted and summed according to the weight ratio of the formula.
[0037] Each embodiment and comparative example was tested in 5 heats. The carbon yield was the arithmetic mean of the 5 heats and was rounded to one decimal place.
[0038] The fluctuation range refers to the range of carbon yield under five repeated furnace tests for the same carbon raiser product, calculated using the following formula: Δη = η max - η min In the formula: Δη is the fluctuation range (%); η max The maximum carbon yield (%) in 5 furnaces; η min This is the minimum carbon yield (%) in 5 furnaces.
[0039] The fluctuation range is rounded to one decimal place. Abnormal furnace runs caused by equipment failure or operational errors are excluded from the test.
[0040] As shown in Table 2, the carbon refining agent prepared using this invention improves the carbon yield compared to the dry mechanical mixing process, and reduces the fluctuation range of the carbon refining rate. The carbon yield is negatively correlated with the spacing between local anchor points; adjacent anchor points are more likely to overlap at their spreading fronts to form a quasi-continuous wetting layer.
[0041] In this invention, after the carbon raiser particles are added to molten steel, polyvinyl alcohol (PVA) undergoes instantaneous thermal decomposition at the high temperature of the molten steel. During the drying process, PVA migrates and accumulates on the particle surface, forming a gradient distribution with a higher content on the outer layer than inside. Thermal decomposition proceeds from the surface to the interior, driving the particles to rapidly disintegrate from the outside in, releasing graphite-silicon carbide interface composite microparticles and their aggregates. The physical contact surfaces formed between graphite particles during filter cake pressing lose their constraint after PVA decomposition and separate under the turbulent shearing of the molten steel. Subsequently, the graphite surface is exposed to the molten steel, further increasing the effective carbon dissolution area.
[0042] Each graphite particle has densely distributed silicon carbide microparticles on its surface facing the pores, with a local average spacing of 2–9 μm. Liquid steel preferentially establishes contact with and dissolves the silicon carbide microparticles, forming a near-carbon-saturated, silicon-containing Fe-Si-C local melt. This melt has a much smaller wetting angle on graphite than pure iron, spreading from each silicon carbide anchor point to the surrounding graphite surface with an effective spreading radius of approximately several micrometers. In areas with dense anchor points, the spreading fronts of adjacent anchor points overlap, forming a quasi-continuous wetting layer covering the graphite surface. Simultaneously, silicon carbide thermodynamically preferentially reacts with dissolved oxygen in the molten steel over graphite, forming local deoxidation micro-regions around each graphite particle, inhibiting graphite oxidation and burn-off. Polyvinylpyrrolidone and polyvinyl alcohol undergo complete pyrolysis at high temperatures, with carbon dissolving in the molten steel as an effective carbon-enhancing component; the remaining products escape in a gaseous state, without introducing any harmful residual elements.
[0043] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit this application. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of this application. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in this invention should still be covered by the claims of this application.
Claims
1. A granular graphite recarburizer, characterized in that, It is prepared from the following dry materials in the following weight proportions: 80-85 parts of natural flake graphite and 12-20 parts of silicon carbide micro powder; the fixed carbon content of the natural flake graphite is not less than 90%, and the particle size D50 is 0.15-0.50 mm; the purity of the silicon carbide micro powder is not less than 80%, and the particle size D50 is not greater than 0.01 mm; the carbon raiser also includes polyvinyl alcohol and polyvinylpyrrolidone, the amount of polyvinyl alcohol added is 2%-5% of the total weight of the above dry materials on a solid basis, and the amount of polyvinylpyrrolidone added is 0.1%-0.5% of the weight of natural flake graphite; the particle size of the carbon raiser is 8-18 mm.
2. The granular graphite recarburizer according to claim 1, characterized in that, The degree of alcoholysis of the polyvinyl alcohol is 85%–95%, and the degree of polymerization is 500–2000.
3. The granular graphite recarburizer according to claim 1, characterized in that, The degree of graphitization of the natural flake graphite is not less than 90%.
4. A method for preparing a granular graphite recarburizer as described in any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Natural flake graphite, water, and polyvinylpyrrolidone are added to a stirred ball mill and wet-milled until the particle size D50 of the natural flake graphite is 0.15-0.50 mm to obtain graphite ink slurry; the amount of polyvinylpyrrolidone added is 0.1%-0.5% of the weight of the natural flake graphite; (2) Add silicon carbide micro powder to the graphite slurry obtained in step (1), and stir in a high-speed disperser at 1000-3000 rpm for 15-45 minutes to obtain a graphite-silicon carbide co-dispersed slurry; the particle size D50 of the silicon carbide micro powder is not greater than 0.01 mm and the purity is not less than 80%; (3) The co-dispersed slurry obtained in step (2) is dehydrated by a filter press at a pressure of 0.5 to 2.0 MPa to a moisture content of 20% to 30% to obtain filter cake; (4) According to the dry material weight ratio, the filter cake obtained in step (3) and polyvinyl alcohol powder are put into a kneader and kneaded for 15 to 45 minutes to obtain a mixture; the degree of alcoholysis of the polyvinyl alcohol powder is 85% to 95%, the degree of polymerization is 500 to 2000, and its addition amount is 2% to 5% of the total dry material weight on a solid basis; (5) The mixture obtained in step (4) is fed into an extrusion granulator, extruded through a template with an aperture of 8-18 mm, and granulated to obtain wet granules; (6) Dry the wet particles obtained in step (5) until the moisture content is less than 1% to obtain the granular graphite recarburizer.
5. The preparation method according to claim 4, characterized in that, The drying process described in step (6) is multi-stage: first, the particles are dried at 60-90℃ until the moisture content is no more than 5%, and then dried at 110-120℃ until the moisture content is less than 1%.
6. A method of using the granular graphite recarburizer as described in any one of claims 1 to 3, characterized in that, Includes the following steps: In the initial stage of converter tapping, when the tapping volume reaches 0% to 30% of the total tapping volume, 20% to 40% of the total recarburizing agent weight is added to the ladle; the remaining 60% to 80% is added to the ladle with the steel flow via a feeder during the converter tapping process; the total amount of recarburizing agent added is 3 to 7 kg / t steel.
7. The method of use according to claim 6, characterized in that, The applicable tapping conditions are: carbon content in molten steel of 0.05% to 0.15%, total oxygen content in steel of 70 ppm to 150 ppm, and tapping temperature of 1610℃ to 1670℃.